2020
DOI: 10.7759/cureus.7328
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman Disease and Unusual Local Invasive Presentation

Abstract: Rosai-Dorfman disease (RDD) is a rare medical condition with bilateral painless lymphadenopathy. We present the case of a young man diagnosed with a very unique presentation of Rosai-Dorfman disease.A 40-year-old African-American man presented with a firm, non-tender, progressive chest and neck mass appeared three months ago. Imaging of the neck demonstrated an 8.6-cm anterior neck subcutaneous soft tissue mass extending into the anterior mediastinum through the sternum with erosive changes in the sternum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Additionally, in 29 out of 53 cases, there was evidence of extra osseous involvement, particularly in soft tissues, lymph nodes, and sinuses. Nasany RA et al 60 found that RDD involvement was most commonly observed in the dura, followed by the spine, brain parenchyma, orbits, and calvarium.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in 29 out of 53 cases, there was evidence of extra osseous involvement, particularly in soft tissues, lymph nodes, and sinuses. Nasany RA et al 60 found that RDD involvement was most commonly observed in the dura, followed by the spine, brain parenchyma, orbits, and calvarium.…”
Section: Discussionmentioning
confidence: 99%
“…In RDD, the histiocytes tend to stain positive for CD68, CD14, fascin, CD163, HLA-DR, and S100; however, they stain negatively for CD1a. These findings can help to establish the diagnosis of RDD [1][2][3] and rule out other conditions such as Langerhans cell histiocytosis, histiocytic sarcoma, classical Hodgkin lymphoma, melanoma, metastatic carcinomas, and infectious lymphadenopathies [1,4] . The clinical diagnosis of RDD is challenging as the clinical presentation is usually variable, especially the extranodal type in the absence of lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…RDD has shown to have a good prognosis, particularly the cutaneous subtype; however, lower respiratory tract or hepatic involvement is considered a poor prognostic factor. The major causes of mortality include amyloidosis or vital organ involvement [ 4 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment strategies for RDD include an expectative approach and monitoring, corticosteroids (usually prednisone or dexamethasone), surgery for unifocal and/or symptomatic extranodal disease, radiotherapy (with a dose of 30-50 Gy), chemotherapy (Vinca alkaloids, methotrexate, cladribine), or immunomodulatory therapy (thalidomide, lenalidomide, rituximab, imatinib mesylate) [12,14,15].…”
Section: Introductionmentioning
confidence: 99%